RETRACTED: SHREC 2021: 3D point cloud change detection for street scenes - Ku, Tao; Galanakis, Sam; Boom, Bas; Veltkamp, Remco C.; Bangera, Darshan; Gangisetty, Shankar; Stagakis, Nikolaos; Arvanitis, Gerasimos; Moustakas, Konstantinos (Computers & graphics, 2021)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of the author and Editor-in-Chief. The authors identified an error in the original paper with the software that was made publicly available on GitHub, where accidentally the testing was carried out using the training set, instead of the correct test set, and therefore the published test results are invalid. In addition, other minor inaccuracies in the paper were also identifed. The authors intend to correct the errors and resubmit the paper.